Readiness Measurement of IT Implementation in Higher Education Institutions in Indonesia - M, Irfan; S.J, Putra (2020)
This article elaborates the result of the Pilot Study which is related to IT implementation factors at the Higher Education Institution (HEI), a pilot study is used to validate quantitative readiness model of IT implementation. The main objective of this study is examining the factors that influence the readiness of IT implementation in HEI. This study attempts to analyze IT Content factors, Institutional Context, People, Process, Technology, Service Quality and IT Implementation Readiness (ITIR). The sample of data was taken from 150 HEIs throughout Indonesia which was then processed in statistical techniques through PLS-SEM method. The research finding shows that 9 of the 14 hypotheses used as ITIR model construct have a very significant influence on IT implementation on HEI, so that this finding can provide a comprehensive contribution to the literature of ITIR model development.